Las estrategias de enseñanza y su incidencia en la comprensión lectora a los estudiantes de la UE Francisco Huerta Rendon, 2021 - Parraga Santisteban, German Jose (2022)
The research project will allow knowing why reading comprehension deficits occur in sixth grade students of the "Francisco Huerta Rendon" U.E in the city of Babahoyo, province of "Los Ríos". Today it is very important that generations learn to develop cognitive and metacognitive strategies and develop critical thinking that allows them to learn autonomously. It is necessary to measure in students that they understand how important reading comprehension is and what it means to obtain reflective, analytical learning by learning the most important ideas of the text, and relating them to concepts that have new meaning for the reader. The applied methodology was scientific, in addition the analysis was carried out in a quantitative and qualitative way, proceeding to carry out the survey of 45 students which allowed us to establish that the students do not understand what they read, therefore they cannot express themselves critically and reflexively, therefore that a teaching strategy was developed to help improve reading comprehension in sixth grade students of Basic General Education. The purpose of this work is to provide teachers and students with a solid conceptual base, about the mechanisms and intellectual tools, which act when analyzing, inferring, understanding and interpreting written texts. It is recommended that they generate a taste for reading, so that they can establish an adequate sequence, interpretation and analysis. Apply a guide to teaching strategies to develop reading comprehension.